Gertrude Bonnin on Sexual Morality - Lewandowski, Tadeusz (English Studies at NBU, 2021)
This paper examines attitudes to sexual morality held by the Yankton Dakota author and activist Gertrude Bonnin (1876â€“1938), better known by her penname ZitkÃ¡la-Å Ã¡ (Red Bird in Lakota). Bonninâ€™s concerns encompass several themes: the victimization of Indian women, disintegration of Native courtship rituals, sexual threats posed by peyote use, and the predatory nature of Euro-American men. This critique as a whole â€” in which a â€˜white invasion,â€™ in her words, leads to a corruption of Native sexuality â€” sometimes produces inconsistencies, particularly regarding Bonninâ€™s statements on the alleged sexual perils of peyote. Her investigations into the Oklahoma guardianship scandals of the 1920s, however, strongly buttress recent research by Sarah Deer (2015), whose study, The Beginning and End of Rape: Confronting Sexual Violence in Native America, highlights the tragic aspects of Native-white sexual relations under United States settler-colonialism.